(untitled) (Journal of research in medical and health sciences, 2026)
As a revolutionary breakthrough in the field of life sciences, gene editing technology is profoundly reshaping the landscape of medical and pharmaceutical research. This paper systematically explains the molecular mechanisms of gene editing technology, with a particular focus on its application value in core areas such as the construction of precise disease models, the development of innovative gene therapies, targeted drug discovery, and xenotransplantation. It also deepens the analysis of these application scenarios in light of the latest clinical research findings from 2024 to 2025. At the same time, the paper thoroughly explores key challenges in the application of this technology, including off-target effects, immunogenicity, and ethical controversies. It further reviews in detail the current progress in technological optimization strategies and the development of ethical regulatory systems, and proposes future pathways for the coordinated advancement of technological innovation and ethical governance, with the aim of providing more comprehensive theoretical support and practical guidance for the standardized clinical translation of gene editing technology.